Surviving Street Life: A Phenomenological Study on Street Children (Journal of Namibian Studies : History Politics Culture, 2023)
The street children phenomenon is among the major societal problems that need attention, mitigation, and investigation. Hence, this qualitative study was conducted to explore the lived experiences of street children in a city in Negros Occidental, Philippines. Eight street children composed of girls and boys were the participants of this study. Face-to-face in-depth interviews and observation were employed to gather data. Descriptive phenomenological analysis was utilized. Ethical considerations were strictly observed.  It was found that most of the street children in the study are males. Most of them have more than four siblings. Half of them have separated parents and have quit school. They experience varied challenges and employ different coping strategies. The themes that emerged in the study are the following: problematic families, dangerous daily activities, difficult lives, rugby for survival, empty stomach, neglected and problematic schooling, and freedom and autonomy.